Persepsi terhadap Kepemimpinan Kiai, Konformitas dan Kepatuhan Santri terhadap Peraturan Pesantren - Ma'rufah, St; Matulessy, Andik; Noviekayati, IGGA (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The research was conducted to find out the relationship between the perception of Kiai’s leadership and the conformity with the student’s obedience to the Islamic boarding school’s rule. The subject of the research was 115 of the Islamic boarding school’s students at Raudlatul Ulum Arrahmaniyah. The instrument used the obedience scale, perception of Kiai’s leadership scale and conformity scale. analyzing result shows that F value 22,879 and p = 000 (p<0,01), While the result of analyzing determination test shows that the perception to the Kiai’s leadership and conformity give an effective contribution to the student’s obedience to the rule of Islamic boarding school by 23,9 %. Keyword: The obedience, the perception to Kiai’s leadership, Conformity